2006
DOI: 10.3892/or.16.5.1085
|View full text |Cite
|
Sign up to set email alerts
|

The optimal schedule for 5-fluorouracil radiosensitization in colon cancer cell lines

Abstract: To evaluate the optimal schedule of 5-fluorouracil (5-FU) radiosensitization in rectal cancer, we investigated the interaction between radiation and several doses of 5-FU on colon cancer cell lines based on pharmacokinetics of oral fluoropyrimidine. Cellular cytotoxicity in colon cancer cell lines, LoVo, WiDr and Caco-2 was determined, using a WST-8 colorimetric assay, after 24 h exposure to several concentrations of 5-FU and a radiation dose of 5 Gy. Cells were exposed to 5-FU 24 and 0 h before radiation. 5-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
(25 reference statements)
1
17
0
1
Order By: Relevance
“…Ojima et al . ( 34 ) reported that 5FU post‐treatment gradually inhibited mRNA expression of ERCC1 in colon cancer cell lines. Suppression of the protein expression of ERCC1 by 5FU may affect recombination DNA repair efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ojima et al . ( 34 ) reported that 5FU post‐treatment gradually inhibited mRNA expression of ERCC1 in colon cancer cell lines. Suppression of the protein expression of ERCC1 by 5FU may affect recombination DNA repair efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…(20) We next attempted to elucidate the reason why this combination of L-OHP and 5FU contributes to the increasingly cytotoxic effect for MAC cells, and found that the protein expression levels of ERCC1 were down-regulated after treatment of 5FU both in vitro and in vivo. Ojima et al (34) reported that 5FU post-treatment gradually inhibited mRNA expression of ERCC1 in colon cancer cell lines. Suppression of the protein expression of ERCC1 by 5FU may affect recombination DNA repair efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In radiobiologic studies, an upregulation of TP expression was obtained by RT with an increased FU production in tumor tissues (8,9). Capecitabine has demonstrated similar activity with less toxicity than FU as folinic acid-modulated bolus or as protracted infusion, both in metastatic disease and in adjuvant settings; its role has also been investigated as preoperative indication (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In lung cancer, Chen et al showed that low-dose paclitaxel was sufficient for radiosensitization, and delayed irradiation was better than immediate irradiation following drug treatment [206]. In colon cancer cell lines, Ojima and coworkers showed that the cytotoxicity of radiation followed by 5-FU was significantly greater than for 5-FU followed by irradiation [207]. Thus, the optimal clinical schedule should be defined for all radiosensitizers based on preclinical and Phase I clinical trials.…”
Section: Discussionmentioning
confidence: 99%